Anxiety and Depression in Family Members of Critically III Covid-19 Inpatients: Brief Psychological Interventions via Telephone, an Exploratory Study [Response to Letter] - Caballero-Suárez NP; Barrientos-Casarrubias V; Gutiérrez-Velilla E; González Avilés LM; Pérez-López LD; Alvarado-De la Barrera C; Ávila-Ríos S; Mora-Gallegos J (Journal of Multidisciplinary Healthcare, 2023)
Nancy Patricia Caballero-Suárez,1 Vania Barrientos-Casarrubias,1 Ester Gutiérrez-Velilla,1 Lilian Margarita González Avilés,2 Luis Daniel Pérez-López,1,2 Claudia Alvarado-De la Barrera,1 Santiago Ávila-ríos,1 Janella Mora-Gallegos3 1Centro de Investigación en Enfermedades Infecciosas (CIENI), Instituto Nacional de Enfermedades Respiratorias “Ismael Cosío Villegas” (INER), Mexico City, Mexico; 2Programa de Maestría en Psicología, Universidad Nacional Autónoma de México (UNAM), Mexico City, Mexico; 3Programa de Atención a Pacientes y Familiares (PAPyF), Instituto Nacional de Enfermedades Respiratorias “Ismael Cosío Villegas” (INER), Mexico City, MexicoCorrespondence: Nancy Patricia Caballero-Suárez, Departamento de Investigación en Enfermedades Infecciosas (CIENI), Instituto Nacional de Enfermedades Respiratorias (INER), Calzada de Tlalpan 4502, Sección XVI, Tlalpan, Mexico City, 14080, Mexico, Tel +52 155 56667985 ext. 169, Email nancy.caballero@cieni.org.mx